The Evolution of Mathematical Communication Research in Mathematics Education: A Bibliometric Analysis - Miftakhul Jannah; Arif Abdul Haqq; Raman Kumar; Muhammad Hafeez (Edupedia Publisher, 2026)
Purpose – Mathematical communication is a fundamental component of mathematics education that supports conceptual understanding, reasoning, and collaborative learning. Despite the rapid growth of related studies, the field remains fragmented, limiting a comprehensive understanding of its scientific development, intellectual structure, and emerging research directions. This study aimed to map the global research landscape of mathematical communication through bibliometric analysis. Methodology – A bibliometric analysis was conducted on 9,574 English-language journal articles indexed in Scopus. Following the PRISMA guidelines, the study employed VOSviewer to analyse publication trends, co-authorship networks, keyword co-occurrence, Total Link Strength (TLS), overlay visualization, and density visualization. Findings – Publication output has increased markedly since 2015, reflecting the growing importance of mathematical communication in mathematics education. Scientific production remains concentrated in a few countries, while collaboration networks are fragmented. The field is intellectually structured around mathematical communication, collaborative learning, self-regulated learning, cognitive engagement, and higher-order thinking skills. Recent research has shifted towards digital pedagogy and technology-enhanced communication, whereas technology-integrated communication, co-regulated learning, longitudinal studies, and cross-cultural research remain underexplored. Novelty – This study presents the first comprehensive bibliometric mapping that integrates scientific development, intellectual structure, thematic evolution, and research frontiers of mathematical communication research. Significance – The findings provide an evidence-based foundation for future research, instructional innovation, and international collaboration in mathematics education.